TYPE 2 DIABETES MELLITUS IN WOMEN IN THE MARHAMAT DISTRICT OF ANDIJAN REGION (Web of Technology: Multidimensional Research Journal, 2023)
In women from 45 to 59 years old (average age according to the World Health Organization age classification 2023) with a body mass index (BMI) above 25 kg/ m2 living in the Marhamat district of the Andijan region, markers of carbohydrate metabolism (serum glucose - fasting and postprandial, glycosylated hemoglobin and urine glucose) and lipid metabolism - total cholesterol ( OH), triglycerides (TG), lipidogram (low density lipoprotein cholesterol - very low density lipoprotein LDL cholesterol – VLDL cholesterol, the atherogenicity coefficient is significantly higher, and high-density lipoprotein cholesterol - HDL cholesterol is significantly lower than in women with normal body weight. Correlation analysis revealed a significant positive relationship between age, BMI, KA, and serum glucose levels. The assessment of markers of carbohydrate and lipid metabolism should be included in the list of mandatory examinations of middle-aged women and should be strictly individual, based on clinical and anamnestic data. There is a correlation between the progression of carbohydrate metabolism disorders and changes in lipid metabolism in the examined women. The population should be widely informed about the risk factors for the development of type 2 diabetes mellitus, as well as the progression of complications of this disease.